Aggressive and cannibalistic behavior of African catfish larvae: effect of different doses of methyltestosteron injecting to female broodstock and larval stocking densities - Triayu Rahmadiah; Muhammad Zairin Junior; Alimuddin Alimuddin; Iis Diatin (Jurnal Akuakultur Indonesia)
ABSTRACT